Ticari Kazancın Basit Usulde Tesbiti ve Vergileme Süreci - Bayraklı, Hasan Hüseyin (Afyon Kocatepe Üniversitesi, 1999)
4369 sayılı yasanın gelir vergisinde yaptığı önemli değişikliklerden biri de, ticari kazancın tespitinde basit usulün getirilmiş olmasıdır. Basit usulde vergileme, götürü usulde vergilemenin yerine getirilmiştir, basit usulde vergilemede, defter tutma yükümlülüğü dışındaki gerçek usulde vergilendirilen ikinci sınıf tacirlere ilişkin hükümler geçerli olacaktır. Basit usulde vergilenmeye tabi olabilmek için genel ve özel şartların yerine gelmesi gerekir. Ticari faaliyet ortaklık şeklinde ise, ortakların basit usule tabi olması için işyeri kirası ve iş hacmi ölçüleri, ortaklığa ait iş yeri kirası ile ortaklığın iş hacmine göre tespit edilir. Kanunda sayılan faaliyetleri yapan mükellefler basit usulde vergilemeden yararlanamazlar. Basit usulde vergilendirilen mükelleflerin, belge temini ve beyanname verilmesinde, bağlı bulunduğu mesleki kuruluşlar tarafından yardım edilir.

One of the new changes is brought to the income tax law by the law of 4369 is the taxation of commercial profit by the simple way. This system is accepted as to function instead of the lump sum taxation. The simple system includes the rules for "second class merchants" ( taxpayers ) who are taxed according to the real basis taxation and excludes the merchants who are responsible from book keeping. The taxpayer has to hold the general and specific conditions to be able to pay taxes according to this new simple way. If the commercial activity has been ınade by a partnership then the partners’ situation will be determined by the rent of the place of business, and the total transactions in the place of business, and similarly the partnership’s situation will be determined by the rent of the place of business and the partnership’s total transactions. If the taxpayer’s activities are mentioned in the Iaw then those taxpayers shall not be taxed by using the simple way. The taxpayers who are taxed according to the simple way might get help from their professional association in order to have the relevant papers and lodge a return.
Keywords: Ticari Kazanç; Vergileme